Supplementary Table S2 - Litzke, Vivienne; Ottensmann, Meinolf; Forcada, Jaume; Heitzmann, Louise; Hoffman, Joe (Dryad Digital Repository, 2019)
96 microsatellite loci selected for testing, comprising twenty that appeared polymorphic in silico as described by Hoffman and Nichols (2011) plus a further 76 loci that carried at least six repeat units.